FAKTOR â FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN SERANGAN JANTUNG KORONER DI POLIKLINIK KHUSUS JANTUNG RSUP DR. M. DJAMIL PADANG 2017 - Iqbal, Revi Neini; Sari, Rebbi Permata (Jurnal Keperawatan Abdurrab, 2018)
Abstract   Coronary heart diseaseis a diseaseof highcurrentand is theleading cause of death, especially inworld. Based on theinitialresearchstudyof10familiesincludinga family of 7peopledo notknowabout theearly symptoms, attitudesandefforts tocontrolandtreatmentofcoronaryheartdisease, resulting in the risk ofcoronary heartdisease. The purpose ofthe studyto determine thefactors-factors related tothe incidence ofcoronary heart disease. Design research is an analytical technique using cross sectional study, conducted in the department of cardiac clinic of Dr. M. Djamil Padang on 05 May s/d 04 September 2017. Respondent control of coronary heart disease as much as 1557 people. The sample was 94 people simple random sampling analysis data processing through univariate and bivariate. Get research results coronary heart disease events (68,1%), negative attitudes (57,4%) and family measures on the incidence of heart attacks that have a unfavorable action (59,6%). Found a significant relationship between the attitude of the family with the incidence of coronary heart disease (p = 0.003) and asignificant correlation between the actions of the family incidence of coronary heart disease (p = 0.004). The results of this study it can be concluded that there is a significant relationship attitudes and actions of family on the incidence of coronary heart Advice for nurses in the cardiac clinic to improve the delivery of information and services, especially in the provision attitudes and actions towards family understanding of coronary heart disease and control measures in the form of leaflets or counseling. Keywords : attitudes, family action, the incidence of heart attack, heart control, heart coroner.   Abstrak Penyakit jantung koroner merupakan penyakit penyebab kematian nomor satu di dunia. Bedasarkan studi awal penelitian dari 10 orang keluarga 7 orang keluarga diantaranya tidak mengetahui tentang gejala awal, sikap dan upaya pengendalian dan perawatan dari penyakit jantung koroner. Tujuan penelitian untuk mengetahui faktorâfaktor yang  berhubungan dengan kejadian serangan jantung koroner. Desain penelitian adalah analitik dengan menggunakan tehnik penelitian cross sectional, yang dilakukan di poliklinik jantung RSUP Dr. M. Djamil Padang. Penelitian dilakukan pada tanggal 05 Mei s/d 04 September 2017. Populasi adalah keluarga yang mendampingi pasien dengan penyakit jantung koroner. Dengan jumlah populasi 1157 orang. Sampel berjumlah 94 orang simple random sampling pengolahan data melalui analisa data secara univariat dan bivariat.  Hasil penelitian menunjukkan kejadian serangan jantung (68,1%.), sikap negatif (57,4%) tindakan yang tidak baik (59,6%). Di temukan adanya hubungan yang bermakna sikap keluarga dengan kejadian serangan jantung koroner (p=0,003) dan ada hubungan yang bermakna tindakan keluarga terhadap kejadian serangan jantung koroner (p=0,004). Hasil penelitian dapat disimpulkan bahwa ada hubungan yang bermakna antara sikap dan tindakan keluarga terhadap kejadian serangan jantung koroner. Peneliti menyarankan kepada perawat di poliklinik jantung untuk dapat memberikan penyuluhan tentang pemahaman sikap, dan tindakan keluarga terhadap penyakit jantung koroner dan upaya pengendaliannya.. Kata Kunci: sikap, tindakan keluarga, kejadian serangan jantung, pengendalian, jantung korener